Transformasi Pendidikan Bagi Anak Berkebutuhan Khusus - Sari, Herlina (Journal of Innovation in Teaching and Instructional Media, 2025)
Children with special needs (ABK) face many challenges in accessing equal and quality education. To support their needs, adaptive and inclusive educational changes are needed based on understanding diversity of abilities. The importance of inclusive education as a form of change, including a flexible curriculum, the use of learning support technology, and the role of competent teachers in dealing with students and children with special needs. This research analyzes the development of a comprehensive learning model and its impact on the academic and social emotional development of ABK. We use a qualitative approach with in-depth interviews with teachers and parents, as well as direct observation of the learning process. In this study, transformation of ABK education requires three elements: development of an adaptive curriculum, increasing teacher capacity in special education, and strengthening collaboration between schools and families. These results highlight the importance of a holistic approach in transforming ABK education, apart from focusing on academic aspects but also paying attention to social and emotional aspects. This study provides practical recommendations for developing inclusive education policies in Indonesia.